2018
DOI: 10.1590/18069657rbcs20170079
|View full text |Cite
|
Sign up to set email alerts
|

Is Composting a Route to Solubilize Low-Grade Phosphate Rocks and Improve MAP-Based Composts?

Abstract: Is composting a route to solubilize low-grade phosphate rocks and improve map-based composts? Rev Bras Cienc Solo. 2018;42:e0170079.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Depending on the locality and the availability of organic resources, P availability of organic materials could be enhanced by addition of RP. Various reviews and experiments from across the globe have reported on several on-farm and off-farm sourced organic materials used in co-composting with RP [24,30,31]. Since the type of organic matter used directly affects the P availability, the effectiveness of various RP enriched compost materials has been investigated [32].…”
Section: Increasing P Availability Of Rp For Organic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the locality and the availability of organic resources, P availability of organic materials could be enhanced by addition of RP. Various reviews and experiments from across the globe have reported on several on-farm and off-farm sourced organic materials used in co-composting with RP [24,30,31]. Since the type of organic matter used directly affects the P availability, the effectiveness of various RP enriched compost materials has been investigated [32].…”
Section: Increasing P Availability Of Rp For Organic Systemsmentioning
confidence: 99%
“…Since the type of organic matter used directly affects the P availability, the effectiveness of various RP enriched compost materials has been investigated [32]. The organic materials used in conjunction with RP range from cereal straws/residues [33,34] to shrub/tree or other plant leaves [35], from by-products of industrial crops [36] to chicken, cow or sheep manures [37][38][39][40], as well as vermicompost [35,41] or a combination of one or more of these resources [30]. Organic materials or manures are generally co-composted with RP to facilitate acidulation of RP, but in some cases are just mixed with RP and applied directly without composting, yet with lower effectiveness [38,42].…”
Section: Increasing P Availability Of Rp For Organic Systemsmentioning
confidence: 99%
“…About 45 L of the mixture from each mixing ratio or treatment was left for 38 days in 50 L compost bins, according to Li et al [16]. Samples were collected each time the compost mixtures were turned on 0, 4,8,12,16,20,24,31, and 38 days. At each sampling date, a homogeneous sample of 200 g was taken from the top, middle, and bottom of each compost bin using the quartering method [15,17].…”
Section: Experiments Design and Proceduresmentioning
confidence: 99%
“…Total P was determined using the Automated Discrete Analyzers Model Smart Chem 200 after digestion with H 2 SO 4 -H 2 O 2 . Water-soluble P contents were determined by the method of Maluf et al [24]. Citric acid-P was extracted by stirring the mixture with a 2% citric acid solution for 30 min, in a sample to solution ratio of 1:20 (w/v), according to the Chinese standard of organic fertilizers [25].…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation